GDP and environment pressure: the role of energy in Latin America and The Caribbean - Zilio, Mariana Ines (2011)
This paper analyzes the relationship between economic growth and energy consumption for a sample of 21 Latin American and Caribbean countries during the 1970-2007 period. The investigation is made on the bases of the Energy Environmental Kuznets Curve (EEKC) hypothesis, using a panel data analysis. Energy consumption at aggregate level is used as an indicator of human environmental pressure and GDP per capita as an indicator of economic activity. Based in a cointegration approach, our results does not support the existence of a stable long run relationship between the series, rejecting the validity of such hypothesis for the selected sample over the 1970-2007 period. © 2011 Elsevier Ltd.